Spatial Mechanisms for Segregation of Competing Sounds, and a Breakdown in Spatial Hearing - Middlebrooks, John C.; Waters, Michael F. (Frontiers in Neuroscience, 2020)
We live in complex auditory environments, in which we are confronted with multiple competing sounds, including the cacophony of talkers in busy markets, classrooms, offices, etc. The purpose of this article is to synthesize observations from a series of experiments that focused on how spatial hearing might aid in disentangling interleaved sequences of sounds. The experiments were unified by a non-verbal task, “rhythmic masking release”, which was applied to psychophysical studies in humans and cats and to cortical physiology in anesthetized cats. Human and feline listeners could segregate competing sequences of sounds from sources that were separated by as little as ~10°. Similarly, single neurons in the cat primary auditory cortex tended to synchronize selectively to sound sequences from one of two competing sources, again with spatial resolution of ~10°. The spatial resolution of spatial stream segregation varied widely depending on the binaural and monaural acoustical cues that were available in various experimental conditions. This is in contrast to a measure of basic sound-source localization, the minimum audible angle, which showed largely constant acuity across those conditions. The differential utilization of acoustical cues suggests that the central spatial mechanisms for stream segregation differ from those for sound localization. The highest-acuity spatial stream segregation was derived from interaural time and level differences. Brainstem processing of those cues is thought to rely heavily on normal function of a voltage-gated potassium channel, Kv3.3. A family was studied having a dominant negative mutation in the gene for that channel. Affected family members exhibited severe loss of sensitivity for interaural time and level differences, which almost certainly would degrade their ability to segregate competing sounds in real-world auditory scenes.